Between Decolonization and Human Capital. Reflections Toward the Expected Role of the Teacher in the Chile Post Transition - Troncoso-Pérez, Patricia E. (2020)
The relationship between socioeconomic mobility and school levels has been thematized since the generalization of modern institutionalized education systems. The demand for Chilean quality education is associated with exitism and the formation of Human Capital, crashing with mismatches between public policies, the crisis of legitimization of public education, and the Latin American epistemic advance that influences the pedagogical exercise through critical pedagogy or decolonization as a new way of organizing / re-creating knowledge. Thus, the teacher is required from two dichotomous currents, which makes him a vortex with unusual edges. This article of reflection seeks to expose some aspects of these contradictions, addressing the theory of Human Capital in education and the decolonization of pedagogy, in relation to the expected role of teachers in Chile.